1992
DOI: 10.1002/j.1460-2075.1992.tb05400.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequences directing dihydrolipoamide dehydrogenase (E3) binding are located on the 2-oxoglutarate dehydrogenase (E1) component of the mammalian 2-oxoglutarate dehydrogenase multienzyme complex.

Abstract: Sequences located in the N‐terminal region of the high M(r) 2‐oxoglutarate dehydrogenase (E1) enzyme of the mammalian 2‐oxoglutarate dehydrogenase multienzyme complex (OGDC) exhibit significant similarity with corresponding sequences from the lipoyl domains of the dihydrolipoamide acetyltransferase (E2) and protein X components of eukaryotic pyruvate dehydrogenase complexes (PDCs). Two additional features of this region of E1 resemble lipoyl domains: (i) it is readily released by trypsin, generating a small N‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…In addition, anti-E3BP (PDC) serum (B, lane 3) also recognizes E1 of OGDC (lane 4).Two minor degradation products of E3BP are also highlighted by the anti-E3BP serum (lane 3). As indicated, sequence similarities between E1 of OGDC and the E2 and E3BP subunits of PDC have been documented previously (13); this immunological evidence confirms that these polypeptides possess shared antigenic determinants and are likely to contain equivalent domains with common or overlapping functions.…”
Section: Immunological Analysis Of Similarities Between the E1 Componsupporting
confidence: 77%
See 4 more Smart Citations
“…In addition, anti-E3BP (PDC) serum (B, lane 3) also recognizes E1 of OGDC (lane 4).Two minor degradation products of E3BP are also highlighted by the anti-E3BP serum (lane 3). As indicated, sequence similarities between E1 of OGDC and the E2 and E3BP subunits of PDC have been documented previously (13); this immunological evidence confirms that these polypeptides possess shared antigenic determinants and are likely to contain equivalent domains with common or overlapping functions.…”
Section: Immunological Analysis Of Similarities Between the E1 Componsupporting
confidence: 77%
“…Previous biochemical studies on mammalian OGDC detected significant sequence similarities between the N terminus of its E1 component and the E2 and E3BP subunits of eukaryotic PDCs corresponding to the N-terminal regions of their peripherally located lipoyl domains (13). Similar investigation of the N terminus of the E1Ј fragment indicated that these similarities extended into the interior of E1 and that the tryptic cleavage site was situated at a putative subunit-binding domain.…”
Section: Immunological Analysis Of Similarities Between the E1 Componmentioning
confidence: 79%
See 3 more Smart Citations